2021
DOI: 10.1038/s42003-021-02743-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of metal ions in the selective inhibition of oncogenic variants of isocitrate dehydrogenase 1

Abstract: Cancer linked isocitrate dehydrogenase (IDH) 1 variants, notably R132H IDH1, manifest a ‘gain-of-function’ to reduce 2-oxoglutarate to 2-hydroxyglutarate. High-throughput screens have enabled clinically useful R132H IDH1 inhibitors, mostly allosteric binders at the dimer interface. We report investigations on roles of divalent metal ions in IDH substrate and inhibitor binding that rationalise this observation. Mg2+/Mn2+ ions enhance substrate binding to wt IDH1 and R132H IDH1, but with the former manifesting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(93 citation statements)
references
References 71 publications
7
86
0
Order By: Relevance
“…Consistent with prior studies on IDH1 R132H and R132C, all the recombinant proteins were predominantly dimeric in solution (Supplementary Fig. 1d–f ) and likely copurify with two NADPH molecules (as reported for IDH1 wt and R132H 18 , and shown for IDH1 R132C, Supplementary Fig. 1g/h ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with prior studies on IDH1 R132H and R132C, all the recombinant proteins were predominantly dimeric in solution (Supplementary Fig. 1d–f ) and likely copurify with two NADPH molecules (as reported for IDH1 wt and R132H 18 , and shown for IDH1 R132C, Supplementary Fig. 1g/h ).…”
Section: Resultssupporting
confidence: 89%
“…To investigate the mechanism of IDH1 S280F mediated inhibitor resistance, we used established protocols 17 , 18 to produce highly purified forms of recombinant IDH1 R132C/S280F and R132H/S280F and, for comparison, IDH1 R132C, IDH1 R132H, IDH1 wildtype (wt), IDH1 S280F (without IDH1 R132C or R132H) and IDH1 R132H/Q277E (Supplementary Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 8 Kinetic and structural analyses of the mutIDH1s have revealed that substitution of an active-site arginine (R132 IDH1) correlates with a lowered affinity for isocitrate and the NADPH-dependent ability to reduce 2-OG to R -2-HG. 6 , 7 , 8 , 162 However, it has been shown that, when observed with NMR-based enzyme assays 163 rather than a fluorescence-based assay, 164 mutIDH1 R132H is capable of producing R -2-HG from isocitrate. 163 At least in studied cases, mutIDH2 does not appear to bind to or dominantly inhibit WT IDH2 165 and does not require WT IDH2 or IDH3 to produce R -2-HG.…”
Section: R- 2-hg Biosynthesis Is Linked To Idh1 and Idh2 Mutationsmentioning
confidence: 99%
“… 6 , 7 , 8 , 162 However, it has been shown that, when observed with NMR-based enzyme assays 163 rather than a fluorescence-based assay, 164 mutIDH1 R132H is capable of producing R -2-HG from isocitrate. 163 At least in studied cases, mutIDH2 does not appear to bind to or dominantly inhibit WT IDH2 165 and does not require WT IDH2 or IDH3 to produce R -2-HG. 166 Cytosolic mutIDH1, however, has been reported to rely on co-expression with WT IDH1 to elevate intracellular 2-HG, 166 , 167 , 168 but that substrate (2-OG and NADPH) is likely not channeled from WT IDH1 to mutIDH1 in a heterodimer.…”
Section: R- 2-hg Biosynthesis Is Linked To Idh1 and Idh2 Mutationsmentioning
confidence: 99%
“…allosteric) inhibition mechanisms have been identified, e.g. in recent work on allosteric isocitrate dehydrogenase inhibitors, (52,53) have emerged from empirical screens rather than detailed knowledge of the roles of the overall protein fold in enzyme catalysis.…”
Section: Discussionmentioning
confidence: 99%